Severe immune thrombocytopenia in a critically ill COVID-19 patient - Ziga Martincic; Barbara Skopec; Karla Rener; Matej Mavric; Tomaz Vovko; Matjaz Jereb; Milica Lukic (International Journal of Infectious Diseases, 2020)
The novel coronavirus SARS-CoV-2 can cause a severe and even fatal respiratory illness named COVID-19. Apart from respiratory failure, COVID-19 may be associated with various autoimmune complications. We present a case of a critically ill patient with COVID-19 who developed severe immune thrombocytopenia that was successfully treated with a concomitant use of corticosteroids and intravenous immunoglobulins.